STRATEGI PENGENTASAN KEMISKINAN KAJIAN SISTEMATIS LITERATUR TERHADAP MODEL-MODEL INTERVENSI SOSIAL-EKONOMI - nurfajriah, Firra; fadilah, Desi jihan (Visi Pencerah Nusantara, 2024)
This study systematically reviews socio-economic intervention models within poverty alleviation strategies, emphasizing the integration of micro-level household approaches, contextual sensitivity, and social justice dimensions. Employing a qualitative methodology through a Systematic Literature Review (SLR), the research analyzes peer-reviewed articles published in reputable journals and indexed in Scopus and Dimensions over the past six years. Only studies explicitly addressing socio-economic intervention strategies were included based on strict eligibility criteria. The findings highlight that the effectiveness of interventions is significantly influenced by household-level configurations, spatial diversity, and the adaptive capacity of cross-sectoral integration. Uniform national interventions often fail to address locally embedded vulnerabilities. Furthermore, successful poverty alleviation requires the synergy of financial support, psychosocial protection, and community participation—particularly for vulnerable groups such as children. The results affirm the need to reformulate intervention models toward more contextualized, participatory, and justice-oriented frameworks. This review contributes to filling a critical gap in the literature by integrating technical, spatial, and normative dimensions into the design of effective and sustainable socio-economic interventions.